An Evaluation of the Primary Fourth-Grade Mathematics Textbook in Jordan in the Light of NCTM Standards - Matouq, Nadia Hamlan; Alzboon, Habis Saad (Journal of Educational and Psychological Sciences, 2021)
This study aimed at evaluating the content of the Jordanian mathematics textbook for the elementary fourth-grade in order to find out the extent that the fourth-grade mathematics textbook includes the standards of the American national for Council mathematics teachers (NCTM-2000), which concerned with mathematical operations (problem-solving, reasoning and proof, mathematical communication, Connections mathematical, mathematical representation) from the point of view of mathematical Connections teachers in Ma'an Governorate, thus, to find out the reasons for the low achievement of students in mathematics international tests.In order to fulfill these objectives, the descriptive analytical approach was used, that is a list of (NCTM) standards was prepared and changed into a questionnaire which was applied on a sample consisted of (119) male and female mathematics teachers for the primary fourth grade representing the study community.The results of the study showed that the extent to which the basic (NCTM) standards are included in the mathematics book for the fourth grade was at a moderate percentage on average about (2.76), the mathematical connection standard had the highest availability at (3.10), followed by the mathematical communication standard (3.08), the representation of mathematical operation at (2.99) respectively, and the problem solving standard at (2.51), whereas the reasoning and proof standard had the least representation.The findings also indicated there were statistically significant differences with regard to the experience variable and for the favor of (11-and more) category. Regarding the social gender, it did not have an effect.The study sets out several recommendations such as, developing the mathematics curriculum in the light of national standards, increasing the percentage of (NCTM) standards in the fourth-grade mathematics textbook, and the necessity to focus on issues connected with proof and reasoning, and problem solving.
Keywords: NTCM standards; mathematics textbook evaluation; the primary fourth grade